2014
DOI: 10.1016/j.tem.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivators: servants and masters for control of systems metabolism

Abstract: Coregulator recruitment to nuclear receptors (NRs) and other transcription factors is essential for proper metabolic gene regulation with coactivators enhancing and corepressors attenuating gene transcription. The Steroid Receptor Coactivator (SRC) family is composed of three homologous members (SRC-1, SRC-2, and SRC-3), which are uniquely important for mediating steroid hormone and mitogenic actions. An accumulating body of work highlights the diverse array of metabolic functions regulated by the SRCs, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 85 publications
(138 reference statements)
1
79
0
1
Order By: Relevance
“…Consistent with the classical definition of a transcriptional coactivator as an amplifier and stabilizer of coregulator complexes (2,9,10,14,15), loss of SRC-2 strikingly reduced the recruitment of metabolically responsive proteins to both Gck and G6pc promoters (Fig. 3C).…”
Section: Src-2 Recruits Distinct Coregulator Complexes To Regulate Gcsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the classical definition of a transcriptional coactivator as an amplifier and stabilizer of coregulator complexes (2,9,10,14,15), loss of SRC-2 strikingly reduced the recruitment of metabolically responsive proteins to both Gck and G6pc promoters (Fig. 3C).…”
Section: Src-2 Recruits Distinct Coregulator Complexes To Regulate Gcsupporting
confidence: 83%
“…Published studies from our laboratory, as well as others, have established Steroid Receptor Coactivator 2 (SRC-2) as a powerful pleiotropic metabolic modulator (2). In adipose tissue, SRC-2 is a key regulator of lipolytic (white fat) and thermogenic gene programs (brown fat) (3).…”
mentioning
confidence: 99%
“…Defective growth hormone signaling and estrogen production resulting in short stature and reduced female reproductive function were reported in Src3 −/− mice (Wang et al 2000, Xu et al 2000. These findings established that p160 co-regulators possess certain functional specificity in vivo (recently reviewed in , Stashi et al 2014b. Data obtained from these animal models pertinent to TH signaling and metabolic regulation is discussed below in the sections 'Roles of co-regulators in peripheral tissues' and 'Roles of co-regulators in the funtion of HPT axis and RTH'.…”
Section: Animal Models Of Co-regulator Functionmentioning
confidence: 77%
“…Mouse knockout models identified SRC co-activators as essential regulators of energy homeostasis as they modulate expression of multiple enzymes in different metabolic pathways and tissues , Stashi et al 2014b.…”
Section: Src1 Knockout Micementioning
confidence: 99%
“…Similarly, expression of the gene encoding the estrogen receptor-α (ER-α) in medial preoptic neurons is essential for the performance of maternal behaviors (6). For behavior and other physiological functions, early papers reported that the first molecular event that leads to hormone-facilitated transcription, depends on the binding of ER-α to an estrogen response element (7), followed by the actions of coactivator proteins (8,9). Recent molecular endocrine papers are more ambiguous on the exact order of events (see Some Outstanding Questions, below) (10)(11)(12).…”
mentioning
confidence: 99%